2008
DOI: 10.1086/590186
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter sakazakiiEnhances Epithelial Cell Injury by Inducing Apoptosis in a Rat Model of Necrotizing Enterocolitis

Abstract: SUMMARY Necrotizing enterocolitis (NEC) is an inflammatory intestinal disorder that affects 2–5% of all premature infants. Enterobacter sakazakii (ES), a common contaminant in milk-based powdered infant formula, is implicated as a causative agent of sepsis, meningitis, and NEC in newborn infants with high mortality rates. However, the role of ES in the pathogenesis of NEC is not known to date. Here, we demonstrate for the first time that ES is able to induce clinical and histological NEC in newborn rats. ES wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
108
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 37 publications
(31 reference statements)
3
108
1
Order By: Relevance
“…100,101 Lipopolysaccarides (LPS) is an outer membrane virulence factor of C. sakazakii, which interacts with enterocytes through LPS mediated binding to TLR4 inducing NEC in animals. [102][103][104][105] In the NEC patients, the elevated level of LPS in serum and stools has been reported. [106][107][108][109][110][111] Altogether, these findings raise the intriguing possibility that LPS may engage in the pathogenesis of NEC and the role of TLR4 within the intestinal epithelium seeks detailed consideration.…”
Section: Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…100,101 Lipopolysaccarides (LPS) is an outer membrane virulence factor of C. sakazakii, which interacts with enterocytes through LPS mediated binding to TLR4 inducing NEC in animals. [102][103][104][105] In the NEC patients, the elevated level of LPS in serum and stools has been reported. [106][107][108][109][110][111] Altogether, these findings raise the intriguing possibility that LPS may engage in the pathogenesis of NEC and the role of TLR4 within the intestinal epithelium seeks detailed consideration.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…The invasion studies with human intestinal (INT407) cells showed the contribution of Outer membrane protease cpa Provides resistance against bactericidal activity of serum; activates plasminogen and inactivates a2-AP 65,66 Sialic acid utilization nanAKT Confers in pathogenesis 71 Iron acquisition system iuc Encodes an iron-uptake system mediated by the active siderophorethat plays a role in iron transport and regulation 67,73 Efflux system ibeB Encodes copper and silver resistance cation efflux system facilitating invasion of brain microvascular endothelial cells (BMEC) 23 Proteolytic enzymes zpx Cause cell deformation and rounding of cells 83 Lipopoysaccarides Chromosomal encoded genes Disrupt epithelial tight junctions 91,102 Type III hemolysin hly Hemolytic activity 66,90 both microfilaments and microtubules from host and bacterial ompA. [69][70][71] Mittal and co-workers 72 reported that OmpA-positive isolates breach blood-brain barrier and invade central nervous system (CNS) causing clinical manifestations.…”
Section: Outer Membrane Proteins (Omps)mentioning
confidence: 99%
“…15 A variation of the hyperosmolar formula model supplements lipopolysaccharide into the formula to simulate the bacterial load that is found in neonatal infants who have NEC. 16e19 C. sakazakii has been demonstrated to induce NEC in an experimental rat pup model 20 and has been used to augment both cell and animal models of NEC. 21,22 Furthermore, C. sakazakii resides in the same family (Enterobacteriaceae) which are the most common types of bacteria associated with clinical cultures for patients with NEC.…”
mentioning
confidence: 99%
“…21,23,24 Experimentally, C. sakazakii disrupts normal intestinal morphologic characteristics, induces epithelial inflammation, and causes increased apoptosis both in vivo and in IEC-6 cells, a nontransformed rat small intestinal crypt cell line. 20 Therefore, the use of C. sakazakii to induce NEC provides a clinically relevant experimental model.…”
mentioning
confidence: 99%
See 1 more Smart Citation